Preparation method and application of proton exchange membrane with built-in acid-base interaction groups in molecules

By introducing internal acid-base groups into the proton exchange membrane, the non-arylether polyaromatic hydrocarbon copolymerized substance subexchange membrane is prepared by superacid catalytic polymerization and sulfonation reaction, the problems of poor mechanical properties and high swelling rate in existing membrane materials in electrochemical hydrogen pumps are solved, and membrane materials with high conductivity and low swelling rate are achieved, which are suitable for the long-term operation of electrochemical hydrogen pumps.

CN115678203BActive Publication Date: 2025-04-04HEBEI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211356979.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-01
Publication Date
2025-04-04
Estimated Expiration
2042-11-01

AI Technical Summary

Technical Problem

The existing proton exchange membranes have problems such as high manufacturing cost, poor mechanical properties and high water absorption swelling rate in electrochemical hydrogen pumps, and it is difficult to meet the operation of low voltage and high current conditions.

Method used

By introducing internal acid-base groups into the proton exchange membrane, a non-arylether polyaromatic copolymerized substance sub-exchange membrane is prepared by superacid catalytic polymerization and sulfonation reaction, and the film material is obtained by casting film technology.

Benefits of technology

A proton exchange membrane with high conductivity, low swelling rate and excellent mechanical properties is achieved, which is suitable for the long-term operation of electrochemical hydrogen pumps and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115678203B_ABST
    Figure CN115678203B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a proton exchange membrane with built-in acid-base groups in the molecule and its application, belonging to the technical field of electrochemical hydrogen pump diaphragm materials. The method comprises the following steps: subjecting aromatic monomers and nitrogen heterocyclic ketone monomers to superacid catalytic polymerization to prepare a non-aromatic ether copolymer containing basic nitrogen heterocyclic groups; then subjecting the copolymer with built-in acid-base groups in the molecule to a sulfonation reaction, and finally subjecting the proton exchange membrane with built-in acid-base groups in the molecule to a film casting process. The prepared membrane material has excellent performance, can well balance the contradictory relationship between the ion conductivity, mechanical properties and swelling of the membrane material, and has a good application prospect in electrochemical hydrogen pumps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical hydrogen pump diaphragm materials, and in particular relates to a preparation method and application of a proton exchange membrane with built-in acid-base reaction groups in molecules. Background Art

[0002] With the rapid development of the current economy and society, it has become an urgent task to find green, low-pollution, high-efficiency and environmentally friendly new energy to replace traditional fossil energy. The efficient use of hydrogen energy is in line with people's expectations for environmentally friendly and efficient use of energy.

[0003] Among them, the electrochemical hydrogen compression pump, as a new type of hydrogen compression equipment, has the advantages of no moving parts, simple operation, low energy consumption, high compression efficiency, etc. It can also remove other impurity gases in hydrogen while pressurizing hydrogen, thereby improving the purity of hydrogen (ACS Energy Lett. 2022, 7, 1322-1329), and has attracted much attention from researchers. The membrane electrode assembly (MEA), as the core of the electrochemical hydrogen compression pump, is usually composed of a proton exchange membrane (PEM), a catalyst layer (CLs), and a gas diffusion layer. The proton exchange membrane is the core of the membrane electrode assembly and plays a key role in blocking the reverse permeation of hydrogen on the high-pressure side and proton transmission. The performance of the membrane directly affects the output pressure and operating life of the electrochemical hydrogen pump. At present, the proton exchange membrane faces technical challenges such as high manufacturing cost and poor mechanical properties. Therefore, the research on the proton exchange membrane plays a key role in the application of the electrochemical hydrogen compression pump.

[0004] Commercial perfluorosulfonic acid proton exchange membranes have a full carbon chain structure, which can ensure long-term stable operation in fuel cells and electrochemical hydrogen pumps. However, their high manufacturing cost and the production of highly toxic byproducts during the preparation process limit their widespread application (Membranes (Basel) 2019; 9(7)). Therefore, it is very necessary to develop new polymer ion exchange membranes that can replace perfluorosulfonic acid membranes.

[0005] At present, most reports on non-fluorinated sulfonated polymers are about introducing sulfonic acid groups into polymer materials such as polyphenylene ether (Progress in Polymer Science 33 (2008) 894-915), polyethersulfone (J. Mater. Chem. 2010, 20, 8036–8044) and polyetheretherketone (J. Mater. Chem. A, 2018, 6, 22940), but these polymer proton exchange membrane materials have high water absorption and swelling rate and low electrical conductivity, which often cannot meet the operation of electrochemical hydrogen pumps under low voltage and high current conditions. Zhang et al. found that the introduction of imidazole groups can effectively inhibit the water absorption and swelling of the membrane by blending sulfonated polyetheretherketone with polybenzimidazole (ACS Appl. Energy Mater. 2019, 2, 8207-8218). Therefore, by adding acid-base reaction groups to the molecules, the water absorption and swelling of the membrane can be effectively inhibited under the condition of ensuring high ionic conductivity. Currently, the polymer electrolyte membranes that have been industrially produced on the market all contain ether bonds. Whether in the sulfonation process or in the operation of the hydrogen pump, the breakage of the ether bonds is an unfavorable factor. Therefore, the importance of solving the problem of ether bonds in the polymer main chain is more significant. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing a proton exchange membrane with built-in acid-base groups in the molecule and its application, wherein the method has controllable sulfonation degree, high conductivity, and is conducive to the long-term operation of the electrochemical hydrogen pump.

[0007] To achieve the above object, the present invention proposes the following technical solutions:

[0008] A proton exchange membrane with built-in acid-base interaction groups in the molecule, wherein the general formula of the proton exchange membrane is a copolymer comprising the following repeating structural units:

[0009]

[0010] Wherein, Ar is a group containing an aromatic ring;

[0011] R1 is a basic nitrogen heterocyclic group;

[0012] R2 and R3 are sulfonated and unsulfonated isatin groups, respectively;

[0013] m represents the degree of polymerization, which is a positive integer of 20-300, and the weight average molecular weight is between 5000-1000000;

[0014] x is the degree of substitution of the basic nitrogen heterocyclic group, y is the degree of substitution of the sulfonated isatin group, 0 <x+y<100。

[0015] Furthermore, Ar is any one of the following groups:

[0016]

[0017] Furthermore, the R1 is any one of the following groups:

[0018]

[0019] Further, the R2 is

[0020] Further, the R3 is

[0021] The present invention also provides a method for preparing the proton exchange membrane with the molecular built-in acid-base reaction groups, comprising the following steps: subjecting aromatic monomers and nitrogen heterocyclic ketone monomers (including indigo carmine monomers, indigo carmine mainly functions to introduce -SO3H, rather than as a basic group that reacts with -SO3H, and the basic group that reacts with -SO3H is the R1 part) to superacid catalytic polymerization to prepare a non-aromatic ether poly (arylidene indigo carmine) copolymer containing basic nitrogen heterocyclic groups; then subjecting the copolymer with the molecular built-in acid-base reaction to a sulfonation reaction, and finally subjecting the proton exchange membrane with the molecular built-in acid-base reaction groups to a film casting process.

[0022] Furthermore, the preparation method has the following specific steps:

[0023] 1) At room temperature, an aromatic monomer and an azacyclic ketone monomer are added to trifluoroacetic acid (TFA), stirred vigorously, and cooled in an ice-water bath; trifluoromethanesulfonic acid (TFSA) is added dropwise to the solution at 0°C, and reacted at room temperature for 6-72 hours until the solution becomes viscous. After the reaction is completed, the obtained mixed solution is poured into a poor solvent to obtain a fibrous polymer, which is crushed to remove excess acid, washed to neutrality, and vacuum dried to obtain a polymer;

[0024] 2) adding the obtained polymer to 18M H2SO4 at room temperature to react, controlling the solid content to 3-15wt%, to obtain a lavender fibrous solid polymer, washing to neutrality and then vacuum drying;

[0025] 3) The dried polymer is dissolved in a polar solvent, the concentration of the solution is controlled to be 3-20wt%, impurities are removed by centrifugation, and then a film is cast on a glass plate, heated, and washed with water until neutral, thereby obtaining a proton exchange membrane with built-in acid-base groups in the molecule.

[0026] Furthermore, in step 1), the molar ratio of trifluoroacetic acid to trifluoromethanesulfonic acid is (1-2):(1-15); the molar ratio of the aromatic monomer to trifluoromethanesulfonic acid is (1-2):(5-50).

[0027] Furthermore, in step 1), the poor solvent is one or a mixture of methanol, ethanol, n-propanol, isopropanol and water.

[0028] Furthermore, in step 1), the method for removing excess acid is: removing excess acid in the solution at 60° C. using 1 M potassium carbonate solution.

[0029] Furthermore, in step 1), distilled water is used for washing; the vacuum drying temperature is 60-100° C., and the time is 48 hours.

[0030] Furthermore, in step 2), the reaction temperature is 50-80°C and the reaction time is 3-30h.

[0031] Furthermore, in step 2), distilled water is used for washing; the vacuum drying temperature is 80° C., and the time is 24-48 hours.

[0032] Furthermore, in step 3), the polar solvent is one or a mixture of any proportion of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

[0033] Furthermore, in step 3), the specific operation of the heat treatment is: heat treatment with 1M H2SO4 at 80°C for 24h.

[0034] The present invention also provides an application of a proton exchange membrane having acid-base interaction groups built into the molecule in the preparation of a membrane electrode assembly.

[0035] The present invention also provides an application of a proton exchange membrane having acid-base interaction groups built into a molecule in the preparation of an electrochemical hydrogen pump.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention discloses a proton exchange membrane material for an electrochemical hydrogen pump with high synthesis efficiency and simple operation. The amount of sulfonated group introduced is controlled by reaction time. The prepared membrane material contains a basic nitrogen heterocyclic group that can interact with the sulfonic acid group and has excellent proton transmission ability, mechanical properties and low swelling rate. The absence of aromatic ether bonds in the molecular chain can increase the device operating life of the membrane material.

[0038] (2) The present invention uses a two-step process of high-efficiency acid-catalyzed polymerization and sulfonation to prepare a non-aromatic ether polyaromatic copolymer proton exchange membrane material with built-in acid-base groups in the molecule, further promoting the commercial development of electrochemical hydrogen compression pumps. The prepared polymer has good solubility and good film-forming properties.

[0039] (3) The proton exchange membrane with built-in acid-base interaction groups in the molecule prepared by the present invention is applied to an electrochemical hydrogen pump and has a lower operating voltage under high current density conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 Comparison of the NMR analysis of the copolymer prepared in Example 1 and the polymer prepared in Comparative Example 1;

[0042] Figure 2 Comparison of mechanical properties of the proton exchange membranes prepared in Examples 1 and 2 and the proton exchange membrane prepared in Comparative Example 1;

[0043] Figure 3 Polarization curves of the proton exchange membranes prepared in Examples 1 and 2 and the proton exchange membrane prepared in Comparative Example 1 in an electrochemical hydrogen pump. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] The "normal temperature" mentioned in the present invention refers to 25°C.

[0050] The present invention prepares a non-aromatic ether poly (arylidene indigo) copolymer containing basic nitrogen heterocyclic groups from aromatic monomers and nitrogen heterocyclic ketone monomers (including indigo monomers) through an efficient superacid catalytic polymerization reaction, and then obtains a copolymer with a certain proportion of acid and base groups built into the molecule through a sulfonation reaction, and obtains a proton exchange membrane used in an electrochemical hydrogen pump through a film casting process. The built-in sulfonic acid group of the polymer molecule interacts with the basic nitrogen heterocyclic group to form hydrogen bonds within and between molecules, thereby increasing the intermolecular force, while increasing the proton transfer rate, reducing the swelling rate of the membrane material and thereby improving its mechanical properties. The present invention has a simple synthesis route, and the prepared membrane material has excellent performance, which can well balance the contradictory relationship between the ion conductivity, mechanical properties and swelling of the membrane material, and has a good application prospect in electrochemical hydrogen pumps. The specific technical scheme is as follows:

[0051] A proton exchange membrane with built-in acid-base interaction groups in the molecule, wherein the general formula of the proton exchange membrane is a copolymer comprising the following repeating structural units:

[0052]

[0053] Wherein, Ar is a group containing an aromatic ring;

[0054] R1 is a basic nitrogen heterocyclic group;

[0055] R2 and R3 are sulfonated and unsulfonated isatin groups, respectively;

[0056] m represents the degree of polymerization, which is a positive integer of 20-300, and the weight average molecular weight is between 5000-1000000;

[0057] x is the degree of substitution of the basic nitrogen heterocyclic group, y is the degree of substitution of the sulfonated isatin group, 0 <x+y<100。

[0058] In some preferred embodiments, Ar is any one of the following groups:

[0059] More preferred are biphenyl, p-terphenyl, and 9,9'-dimethylfluorene.

[0060] In some preferred embodiments, the R1 is any one of the following groups:

[0061] More preferred are imidazole-4-carboxaldehyde and isatin, and isatin and imidazole-2-carboxaldehyde.

[0062] In some preferred embodiments, R2 is

[0063] In some preferred embodiments, R3 is

[0064] The present invention also provides a method for preparing the proton exchange membrane with built-in acid-base groups in the molecule, comprising the following steps: subjecting aromatic monomers and nitrogen heterocyclic ketone monomers (including indigo carmine monomers) to superacid catalytic polymerization to prepare a non-aromatic ether poly (arylidene indigo carmine) copolymer containing basic nitrogen heterocyclic groups; then subjecting the copolymer with built-in acid-base groups in the molecule to a sulfonation reaction; and finally subjecting the proton exchange membrane with built-in acid-base groups in the molecule to a film casting process.

[0065] In some preferred embodiments, the preparation method comprises the following specific steps:

[0066] 1) At room temperature, an aromatic monomer and an azacyclic ketone monomer are added to trifluoroacetic acid (TFA), stirred vigorously, and cooled in an ice-water bath; trifluoromethanesulfonic acid (TFSA) is added dropwise to the solution at 0°C, and reacted at room temperature for 6-72 hours until the solution becomes viscous. After the reaction is completed, the obtained mixed solution is poured into a poor solvent to obtain a fibrous polymer, which is crushed to remove excess acid, washed to neutrality, and vacuum dried to obtain a polymer;

[0067] 2) adding the obtained polymer to 18M H2SO4 at room temperature to react, controlling the solid content to 3-15wt%, to obtain a lavender fibrous solid polymer, washing to neutrality and then vacuum drying;

[0068] 3) The dried polymer is dissolved in a polar solvent, the concentration of the solution is controlled to be 3-20wt%, impurities are removed by centrifugation, and then a film is cast on a glass plate, heated, and washed with water until neutral, thereby obtaining a proton exchange membrane with built-in acid-base groups in the molecule.

[0069] In some preferred embodiments, in step 1), the molar ratio of trifluoroacetic acid to trifluoromethanesulfonic acid is (1-2):(1-15), preferably, 1.08:1; the molar ratio of the aromatic monomer to trifluoromethanesulfonic acid is (1-2):(5-50), preferably, 1:10.

[0070] In some preferred embodiments, in step 1), the reaction temperature is room temperature; the reaction time is 6-72 h, preferably 20 h, 24 h, 28 h.

[0071] In some preferred embodiments, in step 1), the poor solvent is one or a mixture of methanol, ethanol, n-propanol, isopropanol and water, preferably anhydrous ethanol.

[0072] In some preferred embodiments, in step 1), the method for removing excess acid is: removing excess acid in the solution at 60° C. using 1 M potassium carbonate solution.

[0073] In some preferred embodiments, in step 1), distilled water is used for washing; the vacuum drying temperature is 60-100° C., preferably 80° C., and the time is 48 hours.

[0074] In some preferred embodiments, in step 2), the reaction temperature is 50-80°C, preferably 50°C; the reaction time is 3-30h, preferably 8h, 10h, 11h, 12h, 14h.

[0075] In some preferred embodiments, in step 2), distilled water is used for washing, and the vacuum drying temperature is 80° C. for 24-48 hours, preferably 24 hours or 48 hours.

[0076] In some preferred embodiments, in step 3), the polar solvent is one or a mixture of any proportion of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone, more preferably dimethyl sulfoxide.

[0077] In some preferred embodiments, in step 3), the specific operation of the heat treatment is: heat treatment with 1M H2SO4 at 80°C for 24h.

[0078] The present invention also provides an application of a proton exchange membrane having acid-base interaction groups built into the molecule in the preparation of a membrane electrode assembly.

[0079] The present invention also provides an application of a proton exchange membrane having acid-base interaction groups built into a molecule in the preparation of an electrochemical hydrogen pump.

[0080] In some preferred embodiments, in the application, the specific preparation steps of the electrochemical hydrogen pump are as follows:

[0081] 1) Fabrication of membrane electrode assembly (MEA): Pt / C catalyst (40 wt%), deionized water, isopropanol and Nafion ionomer solution (5 wt%) were mixed uniformly using magnetic stirring and ultrasonic waves. The well-dispersed catalyst ink was sprayed onto both sides of the proton exchange membrane to form the anode and cathode. The catalyst loading was 0.5 mg cm -2 , and then the catalyst-coated membrane was sandwiched between two pieces of carbon paper and hot-pressed at 2 MPa for 5 min to obtain MEA.

[0082] 2) Set the effective area to 4cm 2 The membrane electrode (MEA) was installed in a single-cell test system. The electrochemical hydrogen pump performance was tested at 60°C under single-side full humidification conditions without back pressure, and the H2 flow rate was 50 sccm. In constant current charging mode, the flow rate was 200 mA cm -2 After fully activated, apply 100-1000 mA cm to the electrochemical hydrogen pump. -2 The current density was 100 mA cm -2 The test was carried out at a rate of 1 / min and points were taken at 1min intervals to record the curve of battery voltage changing with current density.

[0083] Example 1

[0084] This embodiment is mainly prepared by superacid catalytic polymerization of biphenyl, indigo carmine and imidazole-4-carboxaldehyde. The specific structure of the polymer and the experimental steps are as follows:

[0085]

[0086] (1) At room temperature, first dissolve biphenyl (1.54 g, 10.00 mmol), isatin (1.32 g, 9.00 mmol) and imidazole-4-carboxaldehyde (0.10 g, 1.00 mmol) in trifluoroacetic acid (8 mL, 108 mmol) and stir until uniform. Add trifluoromethanesulfonic acid (TFSA) (8.00 mL, 100.00 mmol) dropwise to the solution at 0°C. Then react at room temperature for 24 h. After the reaction is completed, pour the reaction solution into anhydrous ethanol to obtain a fibrous polymer, remove the excess acid in the polymer with 1 M potassium carbonate solution at 60°C, and then wash it with distilled water several times until it is neutral. After drying the obtained polymer in a vacuum drying oven at 80°C for 48 h, weigh it and the weight is 2.59 g, with a yield of 93%;

[0087] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 10 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a purple solid. The degree of sulfonation was calculated to be 90% according to NMR. The weight was 1.02 g and the yield was 82%;

[0088] (3) The obtained polymer was dissolved in a dimethyl sulfoxide solution with a solid content of 5 wt% and then centrifuged, cast on a glass plate, dried at 80°C for 24 h to form a film, then boiled in 500 mL of water at 50°C for 24 h and vacuum dried for 24 h. The film thickness was 52 μm. At room temperature, the swelling rate was 16.53%, the water absorption rate was 20.63%, and the conductivity was 109.81 mS / cm.

[0089] The obtained proton exchange membrane was used in the electrochemical hydrogen pump test, and the specific steps were as follows:

[0090] 1) In the step of manufacturing a membrane / electrode assembly (MEA), Pt / C catalyst (40 wt%), deionized water, isopropanol and Nafion ionomer solution (5 wt%) were mixed uniformly using magnetic stirring and ultrasonic waves. The well-dispersed catalyst ink was sprayed onto both sides of the proton exchange membrane to form the anode and cathode. The catalyst loading was 0.50 mg cm -2 , and then the catalyst-coated membrane was sandwiched between two pieces of carbon paper and hot-pressed at 2 MPa for 5 min to obtain MEA.

[0091] 2) Set the effective area to 4cm 2 The membrane electrode (MEA) was installed in a single-cell test system. The electrochemical hydrogen pump performance was tested at 60°C under single-side full humidification conditions without back pressure, and the H2 flow rate was 50 sccm. In constant current charging mode, the flow rate was 200 mA cm -2 After fully activated, apply 100-1000 mA cm to the electrochemical hydrogen pump. -2 The current density was 100 mA cm -2 The test was carried out at a rate of 1 / min and points were taken at 1min intervals to record the curve of battery voltage changing with current density.

[0092] Example 2

[0093] This embodiment is mainly prepared by superacid catalytic polymerization of biphenyl, indigo carmine and imidazole-4-carboxaldehyde (based on Example 1, the imidazole-4-carboxaldehyde content is increased). The specific structure of the polymer and the experimental steps are as follows:

[0094]

[0095] (1) At room temperature, first dissolve biphenyl (1.54 g, 10.00 mmol), isatin (1.18 g, 8.00 mmol) and imidazole-4-carboxaldehyde (0.19 g, 2.00 mmol) in trifluoroacetic acid (8 mL) and stir until uniform. Add trifluoromethanesulfonic acid (TFSA) (8.00 mL, 100.00 mmol) dropwise to the solution at 0°C. Then react at room temperature for 28 h. After the reaction is completed, pour the reaction solution into anhydrous ethanol to obtain a fibrous polymer, remove the excess acid in the polymer with 1 M potassium carbonate solution at 60°C, and then wash it with distilled water several times until it is neutral. After drying the obtained polymer in a vacuum drying oven at 80°C for 48 h, weigh it and the weight is 2.40 g, with a yield of 88%;

[0096] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 12 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a purple solid. The degree of sulfonation was 80% according to NMR calculation. The weight was 1.04 g and the yield was 85%;

[0097] (3) The obtained polymer was dissolved in a dimethyl sulfoxide solution with a solid content of 5 wt% and then centrifuged, cast on a glass plate, dried at 80°C for 24 h to form a film, then boiled in 500 mL of water at 50°C for 24 h and vacuum dried for 24 h. The film thickness was 43 μm. At room temperature, the swelling rate was 12.10%, the water absorption rate was 15.72%, and the conductivity was 103.97 mS / cm.

[0098] The obtained proton exchange membrane was used in an electrochemical hydrogen pump test, and the specific steps were the same as those in Example 1.

[0099] Example 3

[0100] This embodiment is mainly prepared by superacid catalytic polymerization of biphenyl, indigo carmine and imidazole-4-carboxaldehyde. The specific structure of the polymer and the experimental steps are as follows:

[0101]

[0102] (1) At room temperature, first dissolve biphenyl (1.54 g, 10.00 mmol), isatin (1.32 g, 9.00 mmol) and imidazole-4-carboxaldehyde (0.10 g, 1.00 mmol) in trifluoroacetic acid (8 mL) and stir until uniform. Add trifluoromethanesulfonic acid (TFSA) (8.00 mL, 100.00 mmol) dropwise to the solution at 0°C. Then react at room temperature for 24 h. After the reaction is completed, pour the reaction solution into anhydrous ethanol to obtain a fibrous polymer, remove the excess acid in the polymer with 1 M potassium carbonate solution at 60°C, and then wash it with distilled water several times until it is neutral. After drying the obtained polymer in a vacuum drying oven at 80°C for 48 h, weigh it and the weight is 2.59 g, with a yield of 93%;

[0103] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 8 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a purple solid. The degree of sulfonation was calculated to be 72% according to NMR. The weight was 1.02 g and the yield was 85%;

[0104] (3) The obtained polymer was dissolved in a dimethyl sulfoxide solution with a solid content of 5 wt% and then centrifuged, cast on a glass plate, dried at 80°C for 24 h to form a film, then boiled in 500 mL of water at 50°C for 24 h and vacuum dried for 24 h. The film thickness was 48 μm. At room temperature, the swelling rate was 10.22%, the water absorption rate was 14.32%, and the conductivity was 97.50 mS / cm.

[0105] The obtained proton exchange membrane was used in an electrochemical hydrogen pump test, and the specific steps were the same as those in Example 1.

[0106] Example 4

[0107] This embodiment is mainly prepared by superacid catalytic polymerization of biphenyl, indigo carmine and imidazole-2-carboxaldehyde. The specific structure of the polymer and the experimental steps are as follows:

[0108]

[0109] (1) At room temperature, biphenyl (1.54 g, 10.00 mmol), isatin (1.32 g, 9.00 mmol) and imidazole-2-carboxaldehyde (0.10 g, 1.00 mmol) were first dissolved in trifluoroacetic acid (8 mL) and stirred until uniform. Trifluoromethanesulfonic acid (TFSA) (8.00 mL, 100.00 mmol) was added dropwise to the solution at 0°C. The mixture was then reacted at room temperature for 28 h. After the reaction was completed, the reaction solution was poured into anhydrous ethanol to obtain a fibrous polymer. The excess acid in the polymer was removed with a 1 M potassium carbonate solution at 60°C, and then washed with distilled water several times until neutral. The obtained polymer was dried in a vacuum drying oven at 80°C for 48 h and weighed. The weight was 2.48 g, and the yield was 89%.

[0110] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 11 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a purple solid. The degree of sulfonation was calculated by NMR and the weight was 1.08 g, with a yield of 87%.

[0111] (3) The obtained polymer was dissolved in a dimethyl sulfoxide solution with a solid content of 5 wt% and then centrifuged, cast on a glass plate, dried at 80°C for 24 h to form a film, then boiled in 500 mL of water at 50°C for 24 h and vacuum dried for 24 h. The film thickness was 58 μm. At room temperature, the swelling rate was 14.80%, the water absorption rate was 17.54%, and the conductivity was 106.20 mS / cm.

[0112] The obtained proton exchange membrane was used in an electrochemical hydrogen pump test, and the specific steps were the same as those in Example 1.

[0113] Example 5

[0114] This embodiment is mainly prepared by superacid catalytic polymerization of p-terphenyl, indigo carmine and imidazole-4-carboxaldehyde, and the polymer structure is:

[0115]

[0116] (1) At room temperature, firstly, p-terphenyl (2.30 g, 10.00 mmol), isatin (1.32 g, 9.00 mmol) and imidazole-4-carboxaldehyde (0.10 g, 1.00 mmol) were dissolved in trifluoroacetic acid (8 mL) and stirred until uniform. At 0°C, trifluoromethanesulfonic acid (TFSA) (8.00 mL, 100.00 mmol) was added dropwise to the solution. Then, the mixture was reacted at room temperature for 24 h. After the reaction was completed, the reaction solution was poured into anhydrous ethanol to obtain a fibrous polymer. The excess acid in the polymer was removed with a 1M potassium carbonate solution at 60°C, and then the polymer was washed with distilled water several times until neutral. The obtained polymer was dried in a vacuum drying oven at 80°C for 48 h and weighed. The weight was 3.05 g, and the yield was 86%.

[0117] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 14 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a purple solid. The degree of sulfonation was calculated by nuclear magnetic resonance and was 90%. The weight was 1.07 g and the yield was 90%.

[0118] (3) The obtained polymer was dissolved in a dimethyl sulfoxide solution with a solid content of 5 wt% and then centrifuged, cast on a glass plate, dried at 80°C for 24 h to form a film, then boiled in 500 mL of water at 50°C for 24 h and vacuum dried for 24 h. The film thickness was 49 μm. At room temperature, the swelling rate was 13.51%, the water absorption rate was 16.48%, and the conductivity was 100.87 mS / cm.

[0119] The obtained proton exchange membrane was used in an electrochemical hydrogen pump test, and the specific steps were the same as those in Example 1.

[0120] Example 6

[0121] This embodiment is mainly prepared by superacid catalytic polymerization of p-terphenyl, indigo carmine and imidazole-4-carboxaldehyde (based on Example 5, the sulfonation reaction time is reduced to reduce the amount of sulfonic acid group introduced), and its polymer structure is:

[0122]

[0123] (1) Same as Example 5;

[0124] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 8 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a purple solid. The degree of sulfonation was calculated to be 70% according to NMR. The weight was 1.00 g and the yield was 87%.

[0125] (3) The obtained polymer was dissolved in a dimethyl sulfoxide solution with a solid content of 5 wt% and then centrifuged, cast on a glass plate, dried at 80°C for 24 h to form a film, then boiled in 500 mL of water at 50°C for 24 h and vacuum dried for 24 h. The film thickness was 46 μm. At room temperature, the swelling rate was 10.16%, the water absorption rate was 15.86%, and the conductivity was 95.21 mS / cm.

[0126] The obtained proton exchange membrane was used in an electrochemical hydrogen pump test, and the specific steps were the same as those in Example 1.

[0127] Example 7

[0128] This embodiment is mainly prepared by superacid catalytic polymerization of 9,9'-dimethylfluorene, isatin, and imidazole-4-carboxaldehyde, and its polymer structure is:

[0129]

[0130] (1) At room temperature, 9,9'-dimethylfluorene (1.94 g, 10.00 mmol), isatin (1.32 g, 9.00 mmol) and imidazole-4-carboxaldehyde (0.10 g, 1.00 mmol) were first dissolved in trifluoroacetic acid (8.00 mL) and stirred until uniform. Trifluoromethanesulfonic acid (TFSA) (8.00 mL, 100.00 mmol) was added dropwise to the solution at 0°C. The mixture was then reacted at room temperature for 24 h. After the reaction was completed, the reaction solution was poured into anhydrous ethanol to obtain a fibrous polymer. The excess acid in the polymer was removed with a 1M potassium carbonate solution at 60°C, and then washed with distilled water several times until neutral. The obtained polymer was dried in a vacuum drying oven at 80°C for 48 h and weighed. The weight was 2.77 g, and the yield was 87%.

[0131] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 8 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a blue-purple solid. The degree of sulfonation was calculated to be 70% according to NMR. The weight was 1.01 g and the yield was 87%.

[0132] (3) The obtained polymer was dissolved in dimethyl sulfoxide solution with a solid content of 5 wt% and then centrifuged, cast on a glass plate, and dried at 80°C for 24 h to form a film. The film was then boiled in 500 mL of water at 80°C for 24 h and then vacuum dried for 24 h. The film had a thickness of 59 μm, a swelling ratio of 15.35%, a water absorption ratio of 18.85%, and a conductivity of 104.63 mS / cm.

[0133] The obtained proton exchange membrane was used in an electrochemical hydrogen pump test, and the specific steps were the same as those in Example 1.

[0134] Comparative Example 1

[0135] A polymer that does not contain basic N-heterocyclic aromatic hydrocarbons during homopolymerization is used as a comparative example. The specific structure of the polymer and the experimental steps are as follows:

[0136]

[0137] (1) At room temperature, biphenyl (1.54 g, 10.00 mmol) and isatin (1.47 g, 10.00 mmol) were first dissolved in trifluoroacetic acid (8 mL) and stirred until uniform. Trifluoromethanesulfonic acid (TFSA) (8.00 mL, 100.00 mmol) was added dropwise to the solution at 0°C. The mixture was then reacted at room temperature for 20 h. After the reaction was completed, the reaction solution was poured into anhydrous ethanol to obtain a fibrous polymer. The excess acid in the polymer was removed with a 1 M potassium carbonate solution at 60°C, and then washed with distilled water several times until neutral. The obtained polymer was dried in a vacuum drying oven at 80°C for 48 h and weighed. The weight was 2.85 g, and the yield was 88%.

[0138] (2) The above polymer (1.00 g) was added to 18M H2SO4 (20 mL) at room temperature and reacted at 50°C for 14 h. After the reaction was completed, it was immersed in deionized water and washed with water several times. The obtained polymer was dried in a vacuum drying oven at 80°C for 24 h and then filtered to obtain a purple solid. The degree of sulfonation was calculated to be 100% according to NMR. The weight was 1.12 g and the yield was 91%.

[0139] (3) The obtained polymer was dissolved in dimethyl sulfoxide solution with a solid content of 5wt% and then centrifuged, cast on a glass plate, dried at 80°C for 24h to form a film, then boiled in 500mL of water at 80°C for 24h and vacuum dried for 24h. The film thickness was 44μm. At room temperature, the swelling rate was 24.64%, the water absorption rate was 78.77%, and the conductivity was 81.90mS / cm. It was used for electrochemical hydrogen pump testing.

[0140] The obtained proton exchange membrane was used in an electrochemical hydrogen pump test, and the specific steps were the same as those in Example 1.

[0141] Figure 1 Comparison of the NMR analysis of the copolymer prepared in Example 1 and the polymer prepared in Comparative Example 1; Figure 1 It can be seen that in H f =5.68ppm, and the peak of isopropylidene group was generated, and the integral ratio was consistent with the added amount, which proved the successful synthesis of Example 1.

[0142] Figure 2The mechanical properties of the proton exchange membranes prepared in Examples 1 and 2 are compared with those of the proton exchange membrane prepared in Comparative Example 1. Figure 2 It can be seen that the introduction of basic nitrogen heterocyclic groups increases the tensile strength (stress) due to its built-in acid-base effect, that is, the mechanical properties are enhanced.

[0143] Figure 3 The polarization curves of the proton exchange membranes prepared in Examples 1 and 2 and the proton exchange membrane prepared in Comparative Example 1 in an electrochemical hydrogen pump. Figure 3 It can be seen that the introduction of basic nitrogen heterocyclic groups, due to their built-in acid-base effect, has an effectively lower voltage and better performance under the same current density conditions.

[0144] Table 1 is a data comparison of the water absorption and conductivity of the proton exchange membranes prepared in Examples 1-7 and Comparative Example 1.

[0145] Table 1

[0146]

[0147] As can be seen from Table 1, the introduction of basic nitrogen heterocyclic groups effectively reduces the water absorption rate and swelling rate due to their built-in acid-base effect.

[0148] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A proton exchange membrane with built-in acid-base interaction groups in the molecule, characterized in that: The general formula of the proton exchange membrane is a copolymer comprising the following repeating structural units: Wherein, Ar is a group containing an aromatic ring; R1 is a basic nitrogen heterocyclic group; R2 and R3 are sulfonated and unsulfonated isatin groups, respectively; m represents the degree of polymerization, which is a positive integer of 20-300, and the weight average molecular weight is between 5000-1000000; x is the degree of substitution of the basic nitrogen heterocyclic group, y is the degree of substitution of the sulfonated isatin group, 0 <x+y<100; The specific steps of the preparation method of the proton exchange membrane are as follows: 1) adding an aromatic monomer and a nitrogen heterocyclic monomer to trifluoroacetic acid at room temperature, stirring vigorously, and cooling; continuing to add trifluoromethanesulfonic acid at 0°C, reacting at room temperature until the solution becomes viscous, pouring the obtained mixed solution into a poor solvent after the reaction is completed to obtain a fibrous polymer, crushing and removing excess acid, washing to neutrality, and vacuum drying to obtain a polymer; the aromatic monomer is biphenyl, p-terphenyl or 9,9'-dimethylfluorene; 2) adding the obtained polymer to H2SO4 at room temperature to react, controlling the solid content to 3-15 wt % to obtain a lavender fibrous solid polymer, washing it to neutrality and then vacuum drying it; 3) dissolving the dried polymer in a polar solvent, centrifuging, casting on a glass plate to form a film, heating, and washing to neutrality to obtain a proton exchange membrane with built-in acid-base groups in the molecule; In step 2), the reaction temperature is 50-80°C and the reaction time is 8-30h; The nitrogen heterocyclic monomers are imidazole-4-carboxaldehyde and inatin or inatin and imidazole-2-carboxaldehyde; the molar ratio of inatin to imidazole-4-carboxaldehyde is 9:1 or 4:1; the molar ratio of inatin to imidazole-2-carboxaldehyde is 9:

1.

2. A method for preparing a proton exchange membrane with built-in acid-base interaction groups in molecules as claimed in claim 1, characterized in that: The following steps are involved: 1) adding an aromatic monomer and a nitrogen heterocyclic monomer to trifluoroacetic acid at room temperature, stirring vigorously, and cooling; continuing to add trifluoromethanesulfonic acid at 0°C, reacting at room temperature until the solution becomes viscous, and after the reaction is completed, pouring the obtained mixed solution into a poor solvent to obtain a fibrous polymer, crushing and removing excess acid, washing to neutrality, and vacuum drying to obtain a polymer; 2) adding the obtained polymer to H2SO4 at room temperature to react, controlling the solid content to 3-15 wt % to obtain a lavender fibrous solid polymer, washing it to neutrality and then vacuum drying it; 3) The dried polymer is dissolved in a polar solvent, centrifuged, cast on a glass plate to form a film, heated, and washed to neutrality, thereby obtaining a proton exchange membrane with built-in acid-base groups in the molecule.

3. The method for preparing a proton exchange membrane with built-in acid-base interaction groups in molecules according to claim 2, characterized in that: In step 1), the molar ratio of trifluoroacetic acid to trifluoromethanesulfonic acid is (1-2):(1-15); the molar ratio of the aromatic monomer to trifluoromethanesulfonic acid is (1-2):(5-50).

4. The method for preparing a proton exchange membrane with built-in acid-base interaction groups in molecules according to claim 2, characterized in that: In step 1), the poor solvent is one or a mixture of methanol, ethanol, n-propanol, isopropanol and water.

5. The method for preparing a proton exchange membrane with built-in acid-base interaction groups in molecules according to claim 2, characterized in that: In step 2), the reaction temperature is 50-80°C and the reaction time is 8-30h.

6. The method for preparing a proton exchange membrane with built-in acid-base interaction groups in molecules according to claim 2, characterized in that: In step 3), the polar solvent is one or a mixture of any proportion of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

7. Use of the proton exchange membrane with built-in acid-base interaction groups in the molecule as claimed in claim 1 in the preparation of a membrane electrode assembly.

8. Use of the proton exchange membrane with built-in acid-base interaction groups in the molecule as claimed in claim 1 in the preparation of an electrochemical hydrogen pump.

Citation Information

Patent Citations

  • Novel sulfonated polyisatin aryl polymer structure with spiral structure, and efficient preparation and application of sulfonated polyisatin aryl polymer structure

    CN114716650A